PROFILE OF A JUDGE OF THE SECOND LEVEL OF THE JUDICIAL CAREER BASED ON MANAGERIAL SKILLS - Tamariz Béjar, Eva Luz (2019)
The study is based on the incidence of disciplinary processes of the judges and the need to develop managerial skills. The general objective was to propose the profile of a judge of the second level of the judicial career, based on managerial skills, to reduce disciplinary offenses. In the framework of holistic research, it constitutes a projective study. The research design is descriptive-explanatory, transactional, field and propositive. The study population consisted of the all population, consisting of 43 judges of the second level of a judicial district of Peru. For data collection, documentary analysis was carried out, from which complaints, control interventions and disciplinary sanctions were studied; at the same time, a rating scale was used, which measured the level of development of the managerial skills of the judges. For the data analysis, the basic statistics were used: Frequency distribution tables, bar graphs and linear. The results showed that, the judges of a one judicial district on Perú are in the Basic and middle levels of managerial skills development and that their disciplinary offenses are helped by the need to develop such skills; Therefore, it is possible to affirm that part of the profile of the judge provided for in article 2, numeral 4 of the Law on Judicial Careers No. 29277, “knowledge of the organization and management of the judicial office”, is made up of managerial skills.